2019
DOI: 10.1186/s12917-019-1988-4
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of functional traits with focus on udder health in heifers with divergent paternally inherited haplotypes on BTA18

Abstract: Background A major challenge in modern medicine and animal husbandry is the issue of antimicrobial resistance. One approach to solving this potential medical hazard is the selection of farm animals with less susceptibility to infectious diseases. Recent advances in functional genome analysis and quantitative genetics have opened the horizon to apply genetic marker information for efficiently identifying animals with preferential predisposition regarding health traits. The current study characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…This difference could originate in the differing feed intake capacities of the 2 haplotypes. For technical reasons, it was not possible to record the DMI of the animals in the present study, but a parallel long-term experiment with 6 animals (3 Q and 3 q) showed significantly higher feed intake in Q-heifers (Heimes et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This difference could originate in the differing feed intake capacities of the 2 haplotypes. For technical reasons, it was not possible to record the DMI of the animals in the present study, but a parallel long-term experiment with 6 animals (3 Q and 3 q) showed significantly higher feed intake in Q-heifers (Heimes et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…P < 0.05 was considered significant, and P < 0.1 was considered a statistical tendency. lower milk yield of up to 7.6 (Q) or 6.7 (q) kg of ECM compared with their sisters housed in a conventional loose stall barn fed a high-energy TMR (Heimes et al, 2019). Based on studies in organic farming, it is known that a reduced-energy diet results in reduced milk yield despite similar genetic merit (Langford et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, recently, several association studies revealed consistent results concerning BTA 18 and genetic modulation of functional traits [26][27][28][29]. Data from our work group obtained from the postpartum period of the divergent haplotype uniparous cows [37] and from a parallel long-term trial [38] indicate that although SCC served as a target criterion during the selection process, the metabolic adaption capacity of the uniparous cows seems to play a fundamental role in paving the way for adequate immune response patterns towards immunological challenges.…”
Section: Discussionmentioning
confidence: 60%
“…SCC served as a surrogate trait for mastitis susceptibility, indicating low (Q) or high (q) mastitis susceptibility. At the start of the experiment, no significant differences regarding udder-specific parameters were found between the two haplotypes, although Quniparous cows had shown a lower incidence of metritis, lower blood concentrations of betahydroxbutyrate compared to q-uniparous cows, numerical lower incidence of CM and SCM in the postpartum period and significant differences in SCC as recently published [37][38][39].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation